Surrealism in Budi Darma’s Laki – Laki Pemanggul Goni (The Man Carrying the Sack): A Comparative Study - Harendika, Melania Shinta (Language Circle: Journal of Language and Literature, 2018)
Laki – laki Pemanggul Goni is one of Budi Darma‘s short stories. It was firstly published in Kompas, 26 February 2012, and was then translated by Andy Fuller in 2015. Lontar Foundation published the translated version along with the other translated Budi Darma‘s short stories in a book entitled Conversations. Budi Darma is famous of his surrealist work. It is reflected also in Laki – laki Pemanggul Goni. Therefore, this study was intended to find whether its‘ English version conveyed exactly the same characteristics of surrealism as it was in the original version. Bassnett‘s translation as comparative studies, Popovics‘ types of translation equivalence, and Breton‘s surrealism in literature were implemented as the theoretical framework. This study found that both versions did not convey precisely the identical characteristics of surrealism. The Indonesian version‘s surrealism is stronger than it is in the English version. It might occur because of the cultural gap between the author‘s and the translator‘s.